AC Stark Effect on Vortex Spectra Generated by Circularly Polarized Pulses - Meng Li; Guizhong Zhang; Xin Ding; Jianquan Yao (IEEE Photonics Journal, 2019)
In this paper, we report the results of numerical simulation on vortex-shaped photoelectron momentum spectra of the hydrogen atom irradiated by a pair of time-delayed circularly polarized ultrashort pulses. Spectral alterations including broadening, splitting, and fusion are observed with stronger pulse intensity deploying the quantum wave-packet theory. These alterations of the dynamic interference structure are further investigated to stem from the ac Stark effect, by making the local approximation for an analytical ansatz. In addition, for evaluating the ac Stark effect on the hydrogen atom quantitatively, we propose a nonlinear-curve-fitting algorithm of the ground-state population for extracting the complex Stark coefficient, which we define. We find that the ac Stark effect can be well characterized by the complex coefficient, as supported by the overall agreement between the momentum spectra obtained from the wave-packet theory and the local approximation ansatz. The present research may shed further light on Stark effect in laser atom interactions.